Critical appraisal of a fixed combination of esomeprazole and low dose aspirin in risk reduction - Ravi Vachhani; Doumit Bouhaidar; Alvin Zfass; et al (Dove Medical Press, 2010)
Ravi Vachhani1, Doumit Bouhaidar1, Alvin Zfass1, Bimaljit Sandhu1, Ali Nawras21Division of Gastroenterology, Hepatology and Nutrition, Department of Internal Medicine, Virginia Commonwealth University Medical Center, Richmond, Virginia 23298–0341, USA; 2Division of Gastroenterology, Hepatology and Nutrition, Department of Internal Medicine, The University of Toledo Medical Center, Toledo, Ohio 43606-3390, USAAbstract: Low dose aspirin (≤325 mg) is routinely used for primary and secondary prophylaxis of cardiovascular and cerebrovascular events. The use of low dose aspirin is associated with two-to four-fold greater risk of symptomatic or complicated peptic ulcers. Risk factors associated with low dose aspirin induced gastrointestinal toxicity includes prior history of ulcer or upper gastrointestinal (GI) bleeding, concomitant use of other nonsteroidal anti-inflammatory drugs, corticosteroid or warfarin, dual antiplatelet therapy, Helicobacter pylori (H. pylori) infection, and advanced age. Esomeprazole, like other proton pump inhibitors (PPIs) is very effective in decreasing the risk of aspirin induced gastrointestinal toxicity. Although evidence to support esomeprazole or other PPIs for primary prophylaxis in aspirin induced gastrointestinal toxicity is limited, its role in secondary prophylaxis is well established.Keywords: esomeprazole, proton pump inhibitors, low dose aspirin, gastrointestinal toxicity, gastrointestinal bleeding